THE USE OF THE PICTURE-BASED STORYTELLING METHOD IN DEVELOPING READING INTEREST IN CHILDREN AGED 5-6 YEARS AT CIKAL PAUD - Marsonah; Nuryati; Beni Junedi (Cakrawala Pedagogik, 2026)
This study aims to determine efforts to foster reading interest in children aged 5–6 years through the picture story series method at CIKAL Early Childhood Education Center (PAUD CIKAL), Citangkil District, Cilegon City, Banten Province. The background of this study is based on the low reading interest of children who are more interested in playing than reading or looking at books. The picture story series method is used as an engaging learning medium that is appropriate to the characteristics of early childhood, to stimulate their thinking skills and active involvement in the reading process.This study used a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation of six children in group B, the class teacher, and the principal. The results showed that all children demonstrated a very high interest in reading with the picture story series method, as evidenced by their full attention during reading activities, enthusiasm in discussions, and the ability to retell the story content using pictures. Teachers and the principal also responded positively to the effectiveness of this method. The implementation of the illustrated story series method in reading activities at Cikal Early Childhood Education (PAUD) has demonstrated success in fostering reading interest in children aged 5–6 years. Based on observations of six children, all indicators of reading interest showed excellent results. This method provides visual and verbal stimulation that can capture children's attention, increase active participation in discussions, and encourage children to understand and remember the story content. Images play a significant role in helping children connect the story content to their concrete experiences. It can be concluded that the picture story series method is effective in fostering reading interest in early childhood. Engaging learning media encourages children to be more focused, active, and interested in books. This method can be a fun learning strategy to implement in early childhood education settings.